ELECTRONIC WORD OF MOUTH AND ITS IMPACT ON CONSUMER PURCHASE INTENTIONS: A CONCEPTUAL FRAMEWOR - Sonam Goel,Dr. Anupam Sharma (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
With the immense popularity of social media platforms there is a drastic shift from conventional Word of mouth to electronic word of mouth. This growth of social media helpedthe online user in creating and sharing their reviews and recommendations. This sharing of online reviews has lead to the conceptualization of a new term social commerce, whichhas empowered the consumers to search information about the product conveniently and theirinteraction with other consumersin terms of sharing their feelings and frustrations on the web postings or social media platforms. The consumers can even recommend brands through electronic word of mouth (eWOM) with the reduced physical and psychological cost. The extensive literature survey reveals that still there are gaps ininformation processing and the use of eWOM. The present study will help marketers to understand the importance of e-WOM to manage their resources to attract new customers. The purpose of this paper is to contribute to the literature on electronic word of mouth and purchase intentions by assessing the impact of electronic word of mouth (eWOM) on online purchase intentions of consumers.